Calculation of air conditioning load by ACCAL / Mohd. Rizal Salleh and Zamri Ismail - Salleh, Mohd. Rizal; Ismail, Zamri (1995)
In this report, the basic objective is to present how calculation of heat load for air conditioning system being simplified by using a software, ACCAL. In doing so, we have to lay the ground work of subsequent studies in such fields as heat transfer, fundamentals of thermodynamics and QBasic language programming. Starting with the first chapter, we have explained the need for air conditioning and a discussion about the whole ideas of designing an air conditioning system for buildings especially in Malaysia. We have attempted to cover fairly comprehensively about the basic subject matter of heat load in chapter two. In this chapter, we have stressed what is the design condition and limit (outdoor and indoor). We also clarify how the weather condition standards obtained. The sources of load components discussed deeply in this chapter. Chapter three indicates all the equations involve in calculating heat load. This chapter also indicates what standard Table to be used together with the equations. Chapter four discussed the operation and function of the software, ACCAL.